PENGARUH KOMPETENSI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN KANTOR BPJS KETENAGAKERJAAN JAKARTA MENARA JAMSOSTEK - Hania Alfiany; Freddrick Tiagita P (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2023)
The purpose of this study was to analyze the effect of competence and organizational culture on employee performance at the BPJS Ketenagakerjaan Menara Jamsostek Jakarta office. This research includes quantitative research using explanatory survey methods. The sample in this study were all permanent employees. The results of the study show that simultaneously and partially there is an influence of competence and organizational culture on employee performance at the BPJS Ketenagakerjaan Menara Jamsostek Jakarta Office.